Profiling FLT3 Mutations in Mexican Acute Myeloid Leukemia Pediatric Patients: Impact on Overall Survival - Carolina Molina Garay; Karol Carrillo Sánchez; Luis Leonardo Flores Lagunes; Marco Jiménez Olivares; Anallely Muñoz Rivas; Beatríz Eugenia Villegas Torres; Hilario Flores Aguilar; Juan Carlos Núñez Enríquez; Elva Jiménez Hernández; Vilma Carolina Bekker Méndez; José Refugio Torres Nava; Janet Flores Lujano; et al. (Frontiers in Pediatrics, 2020)
Background: Acute myeloid leukemia (AML) is the second most frequent leukemia in childhood. The FLT3 gene participates in hematopoietic stem cell proliferation. FLT3 mutations are recurrent in AML and influence prognosis. In Mexican pediatric AML patients, FLT3 mutational profile, and their clinical impact have not been evaluated.Aim of the study: This study aimed to identify the profile of FLT3 mutations in pediatric patients with de novo AML and to assess their possible influence on overall survival (OS) and other clinical features.Methods: Massive parallel target sequencing of FLT3 was performed in 80 patients.Results:FLT3 mutations [internal tandem duplication (ITD) or tyrosine kinase domain (TKD)] were identified in 24% of them. OS was significantly lower in FLT3POS cases than in FLT3NEG (p = 0.03). The average OS for FLT3POS was 1.2 vs. 2.2 years in FLT3NEG. There were no significant differences in the children's sex, age, percentage of blasts in bone marrow aspirate, or white blood cell count in peripheral blood at diagnosis between both groups. No differences were identified stratifying by the mutational load (high > 0.4) or type of mutation. The negative effect of FLT3 mutations was also observed in patients with acute promyelocytic leukemia (APL).Conclusions:FLT3 mutational profile is described in Mexican pediatric AML patients for the first time. Mutated FLT3 negatively impacts the outcome of AML patients, even considering the APL group. The clinical benefit from treatment with tyrosine kinase inhibitors in the FLT3POS pediatric patients needs to be assessed in clinical trials. FLT3 testing may contribute to better risk stratification in our pediatric AML patients.